The Realization of Deixis in Students’ Writing at Sekolah Tinggi Keguruan dan Ilmu Pendidikan Muhammadiyah Pringsewu Lampung - Astria, Asri; Mujiyanto, Januarius; Rukmini, Dwi (Universitas Negeri Semarang, 2019)
Through the final product of writing, students can communicate their ideas, thoughts, and feelings to the reader. Deixis is one of the branches in pragmatics and one of the writing components that have to be noticed by the students to communicate the meaning in writing. This study is aimed at finding out the realization of deixis in students’ writing text at STKIP Muhammadiyah Pringsewu Lampung, and also to explain the difficulties faced by the students and teacher roles to overcome the students’ difficulties. The researcher uses descriptive qualitative in analyzing data. There are three methods which are used in this study; they are document, observation, and interview. The results of this study showed that the realization of person deixis is more dominant since the students as the writers position themselves as the main characters of their own stories. Place deixis was realized through demonstrative pronoun, English adverb, and English preposition. The use of the proximal form of place deixis is more dominant rather than the distal form of place deixis. Time deixis was realized through past time, present time, future time, and adverbial of time. Social deixis was also realized through relational social deixis (used in informal situation) and absolute social deixis (used in formal situation). The students used discourse deixis in the form of demonstrative this/that and discourse marker. Further, there were difficulties faced by students in using deixis and the methods that used by the teacher to overcome the students’ difficulties. Hence, it is expected that the findings of this study can improve the students’ knowledge in pragmatics and deixis in general; especially they will apply appropriate deixis in order to develop their writing abilities.